Development of solar cells for IOT applications - Ke, Yanfang (Nanyang Technological University, 2022)
With the idea of a highly instrumented world of intelligent inputs and outputs interacting utilizing Internet data communications concepts and technology, the phrase Internet of Things has become prevalent. Health care, traffic control, automobile safety, energy, agriculture, and manufacturing are just a few of the burgeoning IoT uses. This project will install the final product at Ecolabs Centre of Innovation for Energy. The existing battery-operated LoRa (Long Range Radio) sensor will use an external ambient light energy to directly power an array of sensors by incorporating with an RF transmitter component placed in darker areas. First, a wall panel that is near a lighting fixture will be used to collect light energy and store in battery. The energy in battery will then be transferred through RF transmitter component placed in darker areas through wire. The RF transmitter will send RF energy to its receiver wirelessly and store in sensors battery. This will ensure that sensors can be truly wireless and easily deployable at any place of a building and does not require any manpower to do the battery replacement for the sensors Second, the monitoring system is provided. The battery, as we all know, is the most vital part of any device because it powers the entire system. Subsequently, it is important to keep an eye on the battery's voltage level because improper or excessive charging/discharging might cause battery damage or system failure.